2019
DOI: 10.1097/pr9.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that hydroxyurea is associated with attenuated peripheral sensitization in adults with sickle cell disease

Abstract: Introduction: Hydroxyurea (HU) is a drug that targets the underlying pathophysiology of sickle cell disease (SCD); however, it continues to be an underutilized treatment for adults. Previous research suggests that HU treatment can result in fewer hospital contacts for acute vaso-occlusive pain crises (VOC). Hydroxyurea's impact on non-VOC pain, however, is not well established. Objectives: This study examined whether HU moderated patterns of static and dynamic pain proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…In this study, those who used hydroxyurea and strong opioids were more sensitive to HDT and PPT at the thenar eminence, respectively. This is the opposite to previous findings where SCD subjects on hydroxyurea had higher heat and mechanical pain thresholds compared to SCD subjects not on hydroxyurea (19), but similar to findings that chronic opioid therapy is associated with central sensitization in SCD (20). Higher acute pain scores were associated with being more sensitive to PPT at both the thenar eminence and dorsolateral foot.…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, those who used hydroxyurea and strong opioids were more sensitive to HDT and PPT at the thenar eminence, respectively. This is the opposite to previous findings where SCD subjects on hydroxyurea had higher heat and mechanical pain thresholds compared to SCD subjects not on hydroxyurea (19), but similar to findings that chronic opioid therapy is associated with central sensitization in SCD (20). Higher acute pain scores were associated with being more sensitive to PPT at both the thenar eminence and dorsolateral foot.…”
Section: Discussioncontrasting
confidence: 66%
“…The fight against pain in SCD is studied on several approaches, including drugs already in use in the clinical routine such as Hydroxyurea, Pregabalin, Ketamine, as well as biological ones with blood transfusion and the development of new drugs such as crizanlizumab and of L-Glutamine. 14 , 15 , 16 , 17 , 18 , 19 , 20 In a double-blind, placebo-controlled study, crizanlizumab (humanized anti-P-selectin monoclonal antibody) showed promise as a medication to prevent VOC, although it did not show a reduction in the rate of hospitalization days. 18 , 19 In November 2019, this drug received FDA approval in the USA, being indicated to reduce the frequency of VOC in individuals aged ≥ 16 years and diagnosed with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] For example, the use of hydroxyurea has been associated with lower occurrence of VOE pain compared with those not taking the medication. 14 However, little is known about the impact of treatments, such as hydroxyurea, on the occurrence of persistent or chronic pain over time.…”
mentioning
confidence: 99%
“…Advances in treatments of SCD have shown to improve survival rates, manage disease complications, and prevent the occurrence of acute painful events 11–13. For example, the use of hydroxyurea has been associated with lower occurrence of VOE pain compared with those not taking the medication 14. However, little is known about the impact of treatments, such as hydroxyurea, on the occurrence of persistent or chronic pain over time.…”
mentioning
confidence: 99%